HOW TO IMROVE WRITING SKILLS AND BOOST VOCABULARY IN IELTS - Istamova Shahnoza Ismoil kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The following article, describes information about improvement of writing skills and how to increase the vocabulary in IELTS test. Some effective methods and ways to solve these nuisances are given as examples.